Self-regulation strategies for exercising with overloads - Duca, M.; Alberti, G. (EWF Scientific Magazine, 2020)
In this article, two traditional training overload selection methods have been shown (RM and 1RM%) and two that allow selfregulation based on the athlete`s conditions during the training session. The RPE scale based on repetitions in reserve, from powerlifters training, is a valid tool for selecting overloads in exercises that are interrupted when close to muscle failure. It has thus far been more applied for training of maximal strength and muscle hypertrophy.The relative intensity based on sets and repetitions, developed for the training of weightlifters, involves the use of intensity categories in relation to the maximum overloads identified for each combination of sets and repetitions used for an exercise. Its use has been tested in the context of athletic preparation for individual and team sports, which present a combination of exercises aimed at improving hypertrophy, maximal strength, and muscle power. The coach can then choose the most appropriate load strategy with respect to the practice, experience and goals of the person or group being trained.